The Effect of Smart Government on Governance in Covid-19 Era - Unachukwu Nnedi Obianuju; Mercy Ejovwokeoghene Ogbari; George Uzoma K. Chima (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
The research work looked at the relationship between various dimensions of smart government which are citizen centricity, efficiency, effectiveness and the dimensions of smart governance being strategic dimension, networking and collaboration between institutions. This study made use of a quantitative analytical cross-sectional design. The study made use of the Stakeholder theory. It also made use of the purposive, convenience and simple random sampling technique. A survey was designed for the respondents which was inclusive of one hundred and thirty (130) postgraduate students of Covenant University, Ota, Ogun state and the Statistical package for social sciences was used in running the analysis. According to the findings of this study, smart government could be regarded a foundation for establishing governance by utilizing advanced information and technology for good governance, which is characterized by multiple interrelationships between individuals, government and other decision makers. The sample size and analyses focused majorly on the Postgraduate students of Covenant University. From the findings, the students assert that the governments use of ICT platforms has been able to enhance the resilience of the government and organisations as they have been able to develop aÂ  means to cope, adapt and adjust to this global change. The efficient and effective use of ICT, allowed for networking and collaborative interaction between government and other state and the governments and organizations. This implies that governments ability to take smart and strategic actions in the face of unforeseen and unpredictable challenges through the use of ICT has proven a candid means for the government to efficiently and effectively run any nation state. The findings focus on examining the effect of smart government on governance. The paper is significant in giving insightful directives on the realities of running government in a continuous dynamic environment which factors are unpredictable and gives a guide on how government should be run in the face of untold challenges.